Physicochemical Properties of a New PEGylated Polybenzofulvene Brush for Drug Encapsulation - Marco Paolino; Annalisa Reale; Vincenzo Razzano; Germano Giuliani; Alessandro Donati; Gianluca Giorgi; Antonella Caterina Boccia; Raniero Mendichi; Daniele Piovani; Chiara Botta; Laura Salvini; Filippo Samperi; et al. (MDPI AG, 2019)
A new polymer brush was synthesized by spontaneous polymerization of benzofulvene macromonomer 6-MOEG-9-T-BF3k bearing a nona(ethylene glycol) side chain linked to the 3-phenylindene scaffold by means of a triazole heterocycle. The polymer structure was studied by SEC-MALS, NMR spectroscopy, and MALDI-TOF MS techniques, and the results supported the role of oligomeric initiatory species in the spontaneous polymerization of polybenzofulvene derivatives. The aggregation features of high molecular weight poly-6-MOEG-9-T-BF3k-FE were investigated by pyrene fluorescence analysis, dynamic light scattering studies, and transmission electron microscopy, which suggested a tendency towards the formation of spherical objects showing dimensions in the range of 20−200 nm. Moreover, poly-6-MOEG-9-T-BF3k-FE showed an interesting cytocompatibility in the whole concentration range tested that, besides its aggregation features, makes this polybenzofulvene brush a good polymer candidate for nanoencapsulation and delivery of drug molecules. Finally, the photo-physical features of poly-6-MOEG-9-T-BF3k-FE could allow the biodistribution of the resulting drug delivery systems to be monitored by fluorescence microscopy techniques.